Inequality and social cohesion in Africa: Theoretical insights and an exploratory empirical investigation - Francesco Burchi; Gabriela Zapata-Román (German Institute of Development and Sustainability (IDOS), 2022)
Inequality is bad per se and has adverse effects, among other things, on economic development and the environment. It is also often argued that high and increasing inequalities put societies under stress, which increases the likelihood of social conflicts. However, the literature on this topic is scarce and some of the conclusions are not adequately supported by empirical evidence. This is mainly because there are different definitions and measurements of social cohesion. Moreover, some definitions of social cohesion incorporate inequality, thus making it impossible to examine how these two phenomena interact with one another. This paper analyses both theoretically and empirically, the relationship between inequality and social cohesion. To do so, it employs a recent definition of social cohesion provided by Leininger et al. (2021). According to this definition, social cohesion is composed of three core attributes, namely trust, inclusive identity and cooperation for the common good. These attributes are examined in two dimensions, namely the horizontal (relationship among individuals) and vertical (relationship between individuals and state institutions) dimensions of social cohesion. [...]
Keywords: 330; Inequality; Social cohesion; Trust; Cooperation; Identity; Measurement; Social indicators; Correlation; Africa